Step-by-step explanation:
<h2>a - b = a + (-b)</h2><h2>a + b = a - (-b)</h2>
for any real numbers
Answer:
A. ![\frac{1}{5} log_{3}x +log_{3}y](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B5%7D%20log_%7B3%7Dx%20%2Blog_%7B3%7Dy)
Step-by-step explanation:
We have the expression
![log_{3} (\sqrt[5]{x} *y)](https://tex.z-dn.net/?f=log_%7B3%7D%20%28%5Csqrt%5B5%5D%7Bx%7D%20%2Ay%29)
As these two values are being multiplied, we can separate the two and the sum of them will be equal to the multiplied version
![log_{3}\sqrt[5]{x} +log_{3}y](https://tex.z-dn.net/?f=log_%7B3%7D%5Csqrt%5B5%5D%7Bx%7D%20%2Blog_%7B3%7Dy)
The
can be rewritten as
. This allows us to use the exponent rule. This means that it can be written as
![\frac{1}{5} log_{3}x +log_{3}y](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B5%7D%20log_%7B3%7Dx%20%2Blog_%7B3%7Dy)
There were 29 days in February 1984.
Answer:
6 over 9 = 6/9 11 over 88 = 11/88 6/9 = 0.6667(repeating) 11/88 = 0.125
P.S. Dont fall for those link scams! ;)
Hope this helped! If it did, please give me brainliest! It would help a lot! Thanks! :D
<span>√20 + 6√5
= </span><span>√(4 * 5) + 6√5
= 2</span><span>√5 + 6√5
= </span>√5 (2 + 6)
= 8√5
Hope it helps